Cervical Cancer Patients’ Perceptions of Treatment Experiences at Dr. Moewardi Regional General Hospital, Surakarta, Central Java, Indonesia - La Karman Gojali; Eti Poncorini Pamungkasari; Bhisma Murti; Argyo Demartoto; Revi Gama Hatta Novika; Haryani Saptaningtyas (Journal of Health Promotion and Behavior, 2026)
Background: Cervical cancer is one of the most common cancers affecting women and ranks fourth worldwide. During the course of treatment, cervical cancer patients in Indonesia often face various challenges that may affect their quality of life and treatment outcomes. Some of the main challenges experienced by cervical cancer patients include physical, psychological, social, and economic aspects. This study aimed to explore the experiences of cervical cancer patients while undergoing treatment.Subjects and Method: This was a qualitative study with a phenomenological approach. The study was conducted at Dr. Moewardi Regional General Hospital, Surakarta, Central Java, parti-cular¬ly in the Obstetrics and Gynecology Outpatient Clinic. A total of 20 informants, consist¬ing of 1 key informant, 10 main informants, and 9 supporting informants, were selected using purposive sampling. Data were collected through interviews, observations, and documen¬tation. Data were analyzed using the Miles and Huberman approach.Results: The study identified five themes: (1) the emotional journey of cervical cancer patients during treatment, (2) physical challenges experienced during cervical cancer treatment, (3) socio-economic barriers to undergoing cervical cancer treatment, (4) the role of social and spiritual support in patient resilience, and (5) the benefits of and expectations toward cervical cancer treatment.Conclusion: The perceptions of cervical cancer patients during treatment were not limited to medical aspects alone but also encompassed emotional, social, spiritual, and economic dimensions. Addressing these aspects is essential for improving patients’ quality of life and enhancing adherence to cervical cancer treatment.